Final answer:
To find function values, substitute the given values of t into the function g(t). Evaluating each part, we get g(2) = 21, g(t - 2) = 7t^2 - 34t + 45, and g(t) - g(2) = 7t^2 - 6t - 6.
Step-by-step explanation:
To find the function values, we substitute the given values of t into the function g(t). Let's evaluate each part:
(a) g(2) = 7(2)^2 - 6(2) + 5 = 7(4) - 12 + 5 = 28 - 12 + 5 = 21
(b) g(t - 2) = 7(t - 2)^2 - 6(t - 2) + 5 = 7(t^2 - 4t + 4) - 6(t - 2) + 5 = 7t^2 - 28t + 28 - 6t + 12 + 5 = 7t^2 - 34t + 45
(c) g(t) - g(2) = (7t^2 - 6t + 5) - (7(2)^2 - 6(2) + 5) = 7t^2 - 6t + 5 - 28 + 12 + 5 = 7t^2 - 6t - 6